Legal Analysis of E-Commerce Transactions Based on the ITE Law and Consumer Protection Law in Indonesia - Hermawan, Margin Winaya; Putranto, Rahmat Dwi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2024)
This research aims to find out how the legal position of the parties in the implementation of online arisan and to find out how legal protection for online arisan members who are harmed due to default. The research method used is normative research method. The purpose of this method is to identify legal principles, legal rules, and expert opinions to answer issues related to legal problems, such as the legality of online arisan agreements according to the Civil Code and legal protection for online arisan members in the event of default by one of the parties. From the research conducted, the author obtained the following results: First, the legal position in online arisan consists of the arisan owner as the first party, arisan members as the second party, and the admin or arisan assistant as the third party. If there is a default during the implementation of online arisan, the aggrieved party can choose to resolve the problem through family channels. If the family route is unsuccessful, then dispute resolution must be pursued through legal channels in court by submitting a subpoena. Although the online arisan agreement is unwritten, the agreement is still considered valid. Second, legal protection for online arisan members includes preventive and repressive legal protection. Preventive legal protection for online arisan members is regulated in Article 28 paragraph (1) of Law Number 19 of 2016 Concerning the Amendment to Law Number 11 of 2008, which regulates prohibited acts in electronic transactions, as well as Article 1320 and Article 1338 of the Civil Code, which regulates the provisions of the agreement so that it can be implemented properly. Meanwhile, repressive legal protection is regulated in Article 45 to Article 52 of Law Number 19 of 2016, which regulates sanctions for violation of provisions, as well as Article 1243 of the Civil Code, which discusses compensation due to default.